PI3Kδ Inhibition as a Potential Therapeutic Target in COVID-19 - Palma, Giuseppe; Pasqua, Teresa; Silvestri, Giovannino; Rocca, Carmine; Gualtieri, Paola; Barbieri, Antonio; De Bartolo, Anna; De Lorenzo, Antonino; Angelone, Tommaso; Avolio, Ennio; Botti, Gerardo (Frontiers in Immunology, 2020)
The spread of the novel human respiratory coronavirus (SARS-CoV-2) is a global public health emergency. There is no known successful treatment as of this time, and there is a need for medical options to mitigate this current epidemic. SARS-CoV-2 uses the angiotensin-converting enzyme 2 (ACE2) receptor and is primarily trophic for the lower and upper respiratory tract. A number of current studies on COVID-19 have demonstrated the substantial increase in pro-inflammatory factors in the lungs during infection. The virus is also documented in the central nervous system and, particularly in the brainstem, which plays a key role in respiratory and cardiovascular function. Currently, there are few antiviral approaches, and several alternative drugs are under investigation. Two of these are Idelalisib and Ebastine, already proposed as preventive strategies in airways and allergic diseases. The interesting and evolving potential of phosphoinositide 3-kinase δ (PI3Kδ) inhibitors, together with Ebastine, lies in their ability to suppress the release of pro-inflammatory cytokines, such as IL-1β, IL-8, IL-6, and TNF-α, by T cells. This may represent an optional therapeutic choice for COVID-19 to reduce inflammatory reactions and mortality, enabling patients to recover faster. This concise communication aims to provide new potential therapeutic targets capable of mitigating and alleviating SARS-CoV-2 pandemic infection.